PENINGKATAN KOMPETENSI PENYULUH AGAMA ISLAM DESA CEMPLANG MELALUI KAJIAN PEKANAN MAJLIS NUROZHOLAM - Syaefulloh, Syaefulloh (STAI Darul Qalam Tangerang, 2024)
In reality, Islamic religious instructors as the front guard still need to increase their competence in the religious field through the study of classical books. Apart from that, efforts to provide opportunities for young instructors to appear to provide counseling are very necessary. One of the efforts to increase the competency of religious instructors carried out by religious leaders in the Javilan subdistrict is the implementation of weekly studies of the Nuruzholam Majlis. This article aims to reveal and identify the concept of the weekly Nuruzholam Majlis study, how it is implemented and what impact it has on increasing the competency of Islamic religious instructors in Cemplang village, Javilan subdistrict. The results of the research show that the weekly study program of the Nuruzholam Majlis is a special program implemented to improve the competence of Islamic religious instructors, Koran teachers, ustadz, leaders of Majlis Taklim and Islamic boarding schools through the study of classical books in the fields of fiqh, hadith, tauhid, tafsir and tazkiyatunnafsi. This program is implemented every Saturday from 13.30 to 16.00 by studying the five main books by reading the book word for word, translating word for word using Javanese and Sundanese, then continuing with an explanation using Sundanese. Two books are read by the main muqri, and two are read by the muqri of the participants. The impact of this program is; 1) participants understand the reference book text comprehensively word by word, sentence by sentence and overall meaning; 2) The instructor is able to convey back to the congregation well and is more confident. 3) Communication skills increase, 4) Ability to handle good consultations, 5) Skilled in socializing and guiding them to noble morals